Glycogen storage disease type 1a is associated with disturbed vitamin A metabolism and elevated serum retinol levels. (9th December 2019) - Saeed, Ali; Hoogerland, Joanne A; Wessel, Hanna; Heegsma, Janette; Derks, Terry G J; van der Veer, Eveline; Mithieux, Gilles; Rajas, Fabienne; Oosterveer, Maaike H; Faber, Klaas Nico
Abstract: Glycogen storage disease type 1a (GSD Ia) is an inborn error of metabolism caused by mutations in the G6PC gene, encoding the catalytic subunit of glucose-6-phosphatase. Early symptoms include severe fasting intolerance, failure to thrive and hepatomegaly, biochemically associated with nonketotic hypoglycemia, fasting hyperlactidemia, hyperuricemia and hyperlipidemia. Dietary management is the cornerstone of treatment aiming at maintaining euglycemia, prevention of secondary metabolic perturbations and long-term complications, including liver (hepatocellular adenomas and carcinomas), kidney and bone disease (hypovitaminosis D and osteoporosis). As impaired vitamin A homeostasis also associates with similar symptoms and is coordinated by the liver, we here analysed whether vitamin A metabolism is affected in GSD Ia patients and liver-specific G6pc −/− knock-out mice. Serum levels of retinol and retinol binding protein 4 (RBP4) were significantly increased in both GSD Ia patients and L -G6pc −/− mice. In contrast, hepatic retinol levels were significantly reduced in L -G6pc −/− mice, while hepatic retinyl palmitate (vitamin A storage form) and RBP4 levels were not altered. Transcript and protein analyses indicate an enhanced production of retinol and reduced conversion the retinoic acids (unchanged LRAT, Pnpla2/ ATGL and Pnpla3 up, Cyp26a1 down) in L -G6pc −/− mice. Aberrant expression of genes involved in vitamin A metabolism was associated with reduced basal messenger RNA levels of markers of inflammation ( Cd68, Tnfα, Nos2, Il-6 ) and fibrosis ( Col1a1, Acta2, Tgfβ, Timp1 ) in livers of L -G6pc −/− mice. In conclusion, GSD Ia is associated with elevated serum retinol and RBP4 levels, which may contribute to disease symptoms, including osteoporosis and hepatic steatosis.